LOCALLY SELF-SIMILAR FRACTIONAL OSCILLATOR PROCESSES - LIM, S. C.; LI, MING; TEO, L. P.; Nieuwenhuizen, Theo M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
Fractional oscillator processes of Riemann-Liouville and Weyl type are shown to be locally self-similar. The fractal or Hausdorff dimensions of these processes are determined. Relationship between fractional oscillator processes and the corresponding fractional Brownian motion processes is established.